Effect of cold‐induced changes in physical and chemical leaf properties on the resistance of winter triticale (×Triticosecale) to the fungal pathogen Microdochium nivale. (29th October 2012) - Szechyńska‐Hebda, M.; Hebda, M.; Mierzwiński, D.; Kuczyńska, P.; Mirek, M.; Wędzony, M.; van, A.; Karpiński, S.
<x xml:space="preserve">Abstract</x> This study showed that several mechanisms of the basal resistance of winter triticale to Microdochium nivale are cultivar‐dependent and can be induced specifically during plant hardening. Experiments and microscopic observations were conducted on triticale cvs Hewo (able to develop resistance after cold treatment) and Magnat (susceptible to infection despite hardening). In cv. Hewo, cold hardening altered the physical and chemical properties of the leaf surface and prevented both adhesion of M. nivale hyphae to the leaves and direct penetration of the epidermis. Cold‐induced submicron‐ and micron‐scale roughness on the leaf epidermis resulted in superhydrophobicity, restricting fungal adhesion and growth, while the lower permeability and altered chemical composition of the host cell wall protected against tissue digestion by the fungus. The fungal strategy to access the nutrient resources of resistant hosts is the penetration of leaf tissues through stomata, followed by biotrophic intercellular growth of individual hyphae and the formation of haustoria‐like structures within mesophyll cells. In contrast, a destructive necrotrophic fungal lifestyle occurs in susceptible seedlings, despite cold hardening of the plants, with the host epidermis, mesophyll and vascular tissues being digested and becoming disorganized as a result of the low chemical and mechanical stability of the cell wall matrix. This work indicates that specific genetically encoded physical and mechanical properties of the cell wall and leaf tissues that depend on cold hardening are factors that can determine plant resistance against fungal diseases.